Cyclists & cycling around the world : creating liveable & bikeable cities - Dextre Quijandría, Juan Carlos; Hughes, Mike; Bech, Lotte (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
Cyclists and Cycling Around the World is a visionary book of remarkable breadth, highlighting the increasingly valuable and fascinatingly complex role of the bicycle in contemporary urban life and experience. It contains 25 articles written by leading experts in such fields as, local planning, cycle advocacy and research and is divided into seven chapters on policies and topics relevant to increasing cycling in cities. These topics are as diverse as teaching very young children how to use a bicycle to how a cycle culture was revitalised in China, as well as how cycling affects green urban transportation, social mobility, public health, carbon emissions, urban space and gender equality. The articles detail good practices coming from many parts of the world - from India to Bogota, from Copenhagen to Lima by way of Amsterdam and Oregon, USA. The sub-title of the book, Creating Liveable and Bikeable Cities reflects the vision of the editors as they compiled this wonderful and fascinating selection of articles. These articles will not only inspire professionals but will open the eyes of anyone who has owned or even seen a bike to the increasing significance of pedals, a chain and a saddle in the modern urban world! The book was published in English in November 2013 on the occasion of the III EIMUS Conference on Sustainable Mobility in Lima, Peru as well as in e-book and paper format in Copenhagen.
334 p.:il;26 cm.
Keywords: Ciclismo; Bicicletas; Ciclovías; Transporte urbano; Ecología urbana; https://purl.org/pe-repo/ocde/ford#2.00.00